How to analyze tumor stage data in clinical research - Hu, Zhi-De; Zhou, Zhi-Rui; Qian, Shi (Journal of Thoracic Disease; Vol 7, No 4 (April 28, 2015): Journal of Thoracic Disease, 2015)
Tumor staging serves as an important prognostic factor in cancer patient care. It also plays critical roles in cancer-related clinical research. Aimed to shed lights on how to analyze tumor staging related data and deliver proper interpretation, various statistical methods, from categorical data analysis to modeling techniques, were introduced through the examples. General guidelines were discussed for how to choose proper statistical test with key considerations of research aims, study design, measurement scale of data, proper data summary, type of associations, and underlying assumptions of statistical methods.